Social and environmental risk management in supply chains: a survey in the clothing industry - Matthias Freise; Stefan Seuring (Logistics Research, 2015)
Almost daily, news indicates that there are environmental and social problems in globally fragmented supply chains. Even though conceptualisations of sustainable supply chain management suggest supplier-related risk management for sustainable products and processes as substantial for companies, research on how risk management for environmental and social issues in supply chains is performed has so far been neglected. This study aims at analysing both why companies in the clothing industry are performing management of social and environmental risks in their supply chain and what kind of action they are taking. Based on the literature on sustainable supply chain management and supply chain risk management as well as 10 expert interviews, a conceptual model for risk management in sustainable supply chains was developed. This model was tested in an empirical study in the clothing industry. The data were analysed by structural equation modelling. Results of the research show high statistical significance for the respective conceptual model. The main driver to perform risk management in environmental and social affairs is pressures and incentives from stakeholders. While companies' corporate orientation mainly drives social actions, top management drives environmental affairs for differentiating themselves from competitors.
Keywords: 650; Supply chain management; Sustainability; Risk management; Environmental and social issues; Clothing industry; Structural equation modelling